Systematic study of charge-state and energy dependences of transfer-ionization to single-electron-capture ratios for Fq+ ions incident on He - Ünal, R.; Richard, P.; Ben-Itzhak, I.; Cocke, C. L.; Singh, M. J.; Tawara, H.; Woody, N. (My University, 2007)
This paper presents an investigation of the charge-state and energy dependences of transfer-ionization (TI) and single-electron-capture (SC) processes for fluorine ions (q=4+ to 9+) incident on a supersonic He jet target. The measurements were made for beam energies between 0.5 and 2.5MeV∕u. A recoil ion momentum spectrometer was used to separate TI and SC based on the longitudinal momentum transfer and time of flight of the recoil ions. The cross-section ratios for TI to SC, R=σTI∕σSC, were determined and observed to decrease monotonically with velocity. The values of R were combined with measured total transfer cross sections to deduce the cross sections for both SC and TI. Coupled-channel calculations of the energy dependence of TI and SC for F9++He were compared to the experimental cross sections as well as the values of R. The calculated cross sections were found to be slightly lower and the R values slightly higher than the measured values, but with approximately the same energy dependences. A q2 scaling of the He2++He data was also compared to the present data and was found to give unexpected good agreement.